KONSEP TRANSFORMASI SPASIAL KORIDOR KAMPUNG KAUMAN SEMARANG: INTEGRASI IDENTITAS BUDAYA DAN RELIGI DALAM ARSITEKTUR TRADISIONAL - Sepli Yandri; Yessy Christanti Silaban; Rusydina Sabila Fauzi (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
This study aims to formulate a preservation strategy for Kauman Village in Semarang as a sustainable cultural and religious tourism destination through contextual corridor design. As an embryo of urban growth, Kauman currently faces physical degradation and identity erosion driven by uncontrolled modernization. The research methodology adopts Roger Trancik's integrated urban design theory, incorporating figure/ground (mass and void), linkage (visual-structural connectivity), and place (socio-cultural meaning of space) analyses, which are further synthesized through a SWOT matrix. The results formulate the "Wonderful of Java" design concept, a physical transformation that reintegrates traditional Joglo architecture and Islamic symbolism into the main corridor gates. This layout also offers tactical solutions, including dedicated parking facilities and traditional culinary zoning, to mitigate circulation congestion. The study concludes that spatial interventions rooted in local philosophy effectively preserve the dual "santri" and "Jawa" identity amidst capitalistic shifts, while successfully revitalizing the area's historical character as a religious public space.